Impact of area-wide management for fruit flies on the role of women in mango farming. Issue 1 (November 2021) - Ashari,; Suhaeti, R N; Saliem, H P; Ariningsih, E; Septanti, K S; Maulana, M; Faveri, S D; Johnson, P; Shanmugam, V
Abstract: Studies on women's roles in Indonesian mango farming were rarely conducted. This paper examines the changes made to women's roles in mango production and its benefit distribution for household (HH) needs due to Area Wide Management (AWM) implementation for fruit flies. Data were collected at two villages in Indramayu, West Java, during July and August 2019. The respondents were cooperator farmers who had taken part during the 2010‒2015 AWM project implementation. This study applied a survey method for data collecting using structured questionnaires. The data were descriptively analyzed with a focus on gender perspectives. The study showed that the primary activity of most cooperators was for mango farming. Women had minor roles in pre-harvest and harvest mango farming activities. However, almost all accesses and participations of pre-harvest activities had increased after the implementation of AWM. Women's controls have increased for all activities except for processing and sorting, which had been already high. Adult females took control of financial decision-making on how the mango farming benefit was allocated. There was a higher allocation expense on savings, education and vehicle following the implementation of AWM. The increased women's role in the production and financial decision-making had given promising results in children's education improvements. This study suggested that the agricultural program should involve women as the actors as well as the beneficiaries. The women's involvement in the project was expected to optimize the benefits of the project, and further will ensure its sustainability.